The foundations of embryo's human rights: ethical and juridical considerations - Tarantino, Antonio (Medicina e Morale, 1995)
In these notes the author summarizes the varied and complex doctrinal problems regarding the beginning of individual life. His aim is to show a common denominator, valid for the several ideologics that, directly or indirectly, are behind the many doctrinal hypotheses regarding the beginning of life. According to the author, this must lead us to the embryo's biological statute and to the Jaws on his development. Every sensible discussion on the beginning of human being living intrauterine life should start here. The laws of biological order and its gnoseological definition are strictly linked and, as the author says, scientifically correct. His conclusion is the result of an analysis of the most representative philosophical teachings, in which he points out the need to restare the principles of practical philosophy, both in its Aristotelian interpretation and in the Kantian one. This is the author's theory: there is an intimate, autonomous order in each human being living his intrauterine life even though this order is linked to the mother's one. The same order stays the same during his whole life, from birth to natural death. There is a strong link between the order in each human being and the "metahuman" order, whatever wc call it (trascendent, immanent, material); therefore individual life must be considered inside the rules af this order, the individual order is inviolable as the "metahuman" one, except if we want to profess a libertarian individualism. This inviolable order is sacred for those who accept the religious ethics.